Pengaruh Luas Lubang Pipa Pada Kolom Pendek Dengan Variasi Diameter Lubang Pipa 1½”, 2”, 2½” Dan 3”. - Agus Sugianto; Andi Marini Indriani; Ismail Husein (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2015)
AbstractThe use of holes in the manufacture of a column that serves as the placement of sewer commonly found in multi-storey buildings. Understanding of the construction perpetrators of the ideal aperture area of the column need attention so that the ability of the column structure remains fulfilled and a review of functionality also remains accommodated. This research was conducted in the form of short column with concrete cylinder models which were given hole with varied wide then doing test press. The methodology used in this study with the manufacture of concrete cylinder compressive strength of 20 MPa. and variations in the diameter of the pipe hole Ø 1½